Preparation of Flower-like ZnO Architecture for Photodegradation of Caffeine in Aqueous Solution - Le, Thi Mai; Nguyen, Thi Men; Vu, Anh Tuan (Old Journal, 2018)
The flower-like ZnO architecture was prepared by hydrothermal method. As-synthesized samples were characterized by XRD, SEM, and N₂ adsorption/desorption isotherm. The composition of samples before and after calcination was analyzed by XRD, the precursor was completely transformed to ZnO at 400 °C. The catalytic performance of ZnO was evaluated by the degradation of caffeine in aqueous solution under different irradiation of lights. The degradation efficiency was 97.6 % under UV light in 120 min and it was 100 % under solar light in 60 min. The reaction kinetic of photodegradation of caffeine was studied by first-order kinetic model and the reusability of the ZnO sample was investigated through five cyclic tests.